"Hemping" the drinks: Aromatizing alcoholic beverages with a blend of Cannabis sativa L. flowers. (30th September 2020) - Ascrizzi, Roberta; Iannone, Matteo; Cinque, Giulia; Marianelli, Andrea; Pistelli, Luisa; Flamini, Guido
Highlights: For a greener agriculture, exploiting crop residues is of the utmost importance. Hemp produced for seed and fibre is a multi-purpose crop, whose flowers are discarded. A blend of flowers from 2 industrial hemp cultivars was used to produce artisanal beer and liqueur. The balsamic enrichment of the beer headspace did not alter the overall beer-flavour. The liqueur retained more hemp-derived compounds in its aroma bouquet. Abstract: Cannabis sativa L. is a multi-purpose crop, traditionally used for fibre and seed production, whose cultivation is permitted in Europe for varieties complying with the Δ 9 -tetrahydrocannabinol 0.2% threshold. To face the need for a more sustainable agriculture system, the circularization of the crop industries is of the utmost importance. For hemp, the present study proposes the use of flowers, normally regarded to as crop residues, as further exploitable by-products. A French, 'Futura 75', and a Ukrainian, 'Uso 31', cultivar flowers were used for the extraction of the essential oil (EO) and as flavouring agents of two artisanal alcoholic beverages (a beer and a liqueur). The compositions of the EOs and the beverage headspaces were characterized by GC–MS, then subjected to multivariate statistical analysis. The enrichment of the flavour bouquet was more evident for the liqueur, which retained more hemp-derived compounds. The beer maintained its volatile aroma compounds profile, slightly enriched with more balsamic notes.